Planktic Foraminiferal Assemblages in Surface Sediments From the Subpolar North Atlantic Ocean - Sahoo, Nibedita; Saalim, Syed Mohammad; Matul, Alexander; Mohan, Rahul; Tikhonova, Anna; Kozina, Nina (Frontiers in Marine Science, 2022)
Subpolar North Atlantic (SPNA) Ocean has complex hydrography and moderates the global climate through Atlantic Meridional Overturning Circulation (AMOC). The surface water mass dynamics in SPNA, the upper limb of AMOC, governs the plankton distribution. Specifically, the habitat of modern planktic foraminifera is strongly affected by the SPNA hydrography. In the present study, 25 surface sediment samples from the Labrador Sea to Iceland-Faroe-Shetland Channel (IFSC) were examined for planktic foraminifera distribution along a latitudinal transect at 59.50 °N. Planktic foraminifera distribution followed the transition in water mass structure in the study area from the Sub-Arctic water in the west to warm North Atlantic water in the east. Temperature and salinity are two dominant ecological factors controlling planktic foraminifera assemblages in the region. This hydrographic contrast was also reflected in the ratio of Neogloboquadrina pachyderma/Neogloboquadrina incompta along the transect. Based on the cluster analysis, the planktic foraminifera assemblages could be assigned to three groups. A cold/polar group in the Labrador Sea, a mixed (both cold and warm) group in the Irminger Sea, IFSC and a warmer temperate group in the eastern part of the transect were represented by different planktic foraminifera assemblages. Additionally, a decrease in Globorotalia inflata in the eastern transect and an increase in Turborotalita quinqueloba in the Iceland basin and Irminger Sea was observed in our study when compared with the published dataset. From this, we suggest a shift in planktic assemblages in the SPNA. The present study on the distribution of modern planktic foraminifera can help paleoceanographic reconstructions in the SPNA ocean.